113k views
5 votes
Please don’t skip over me!

show all work

Please don’t skip over me! show all work-example-1

1 Answer

7 votes

Answer:

a,c,d

Explanation:


a. \\4i^9+4i^7\\=4i(i^2)^4+4i(i^2)^3\\=4i(-1)^4+4i(-1)^3\\=4i-4i\\=0\\b.\\2i^(18)-3i^(11)\\=2(i^2)^9-3i(i^2)^5\\=2(-1)^9-3i(-1)^5\\=-2+3i\\c.\\7i^(36)-11i^(11)-11i^9\\=7(i^2)^(18)-11i(i^2)^5-11i(i^2)^4\\=7(-1)^(18)-11i(-1)^5-11i(-1)^4\\=7+11i-11i\\=7\\d.\\8i^(22)-1\\=8(i^2)^(11)-1\\=8(-1)^(11)-1\\=-8-1\\=-9

e.


2i^(27)+4\\=2i(i^2)^(13)+4\\=2i(-1)^(13)+4\\=-2i+4

User Codingwithmanny
by
5.3k points